2020
DOI: 10.1186/s40816-020-00158-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and HPLC quantification of antioxidant profiling of ginger rhizome, leaves and flower extracts

Abstract: Background: In the present era, the attention of nutritionist diverted towards the bioactive entities present in natural sources owing to the presence of health boosting perspectives against lifestyle related disarrays. Methods: In this context, different parts of ginger crop i.e. rhizome, leaves and flower of variety Suravi (ID no. 008) were used for the preparation of ginger extracts with 50% methanol, 50% ethanol and water via rotatory shaker for 45 min. After that, different phytochemical analysis and in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 40 publications
2
21
0
Order By: Relevance
“…Ginger samples recorded the greatest amount of certain molecules, such as quercetin, kaempferol and p-hydroxybenzoic acid. This is consistent with the literature as kaempferol and certain flavonoids comprise a significant portion of the phenolic compounds found within ginger [101]. This is unlike the TPC assay result, clearly demonstrating HPLC's ability to generate higher-quality data.…”
Section: Hplc Quantification Analysissupporting
confidence: 90%
“…Ginger samples recorded the greatest amount of certain molecules, such as quercetin, kaempferol and p-hydroxybenzoic acid. This is consistent with the literature as kaempferol and certain flavonoids comprise a significant portion of the phenolic compounds found within ginger [101]. This is unlike the TPC assay result, clearly demonstrating HPLC's ability to generate higher-quality data.…”
Section: Hplc Quantification Analysissupporting
confidence: 90%
“…Likewise, in vitro study (DPPH scavenging capacity assay) revealed that ethanol, methanol and aqueous extracts of ginger exhibit potent antioxidant activity with ethanolic extract being the most prominent (65.30 ± 2.74%) and aqueous extract being the least. The authors arrived at similar findings when they used Ferric reducing antioxidant potential (FRAP)-the maximum FRAP ability was exhibited in ethanolic extract (102.62 ± 4.28 µmol TE/g) as compared to methanolic (98.14 ± 3.3 µmol TE/g) and water extracts (94.86 ± 3.32 µmol TE/g) [30].…”
Section: Antioxidant Activitymentioning
confidence: 59%
“…The results revealed that the total phenolic concentration in CM extract of ginger rhizome was higher (60.34 ± 0.43 mg gallic acid/g) compared to PE extract (52.17 ± 2.41 mg gallic acid/g), but not significantly different between the treatments [29]. Using methanol, ethanol and water as solvents, Tanweer et al [30] reported total phenolics of ginger rhizome to be 430.72 ± 16.80, 650.44 ± 27.32 and 297.88 ± 10.43 mg GAE/100 g, respectively. With respect to flavonoids an amount of 234.06 ± 9.13, 239.52 ± 10.06 and 218.34 ± 7.64 mg/100 g was detected in methanol, ethanol and water extracts, respectively.…”
Section: Phytochemical Composition Of Gingermentioning
confidence: 93%
See 1 more Smart Citation
“…For example, Ghasemzadeh reported that the total phenolic content for two varieties of young ginger ( Halia Bentong and Halia Bara ) with methanol extraction (Ghasemzadeh et al., 2011) was 10.1 and 13.4 gallic acid equivalent mg/g dry powder, respectively. However, TPC in matured ginger was found to be 4.31 mg gallic acid equivalent/g sample (Tanweer et al., 2020). In our present study, baby ginger (week 1) extract has shown the highest amount of TPC (16.9 mg gallic acid equivalent mg/g dry powder) and TPC was dramatically dropped to 50% when they were harvested after 4 months.…”
Section: Resultsmentioning
confidence: 99%